Meyerhold, as current as relevant - Salas Murillo, Rolando (2021)
Eight decades after their disappearance, Vseolod Emilievic Meyerhold’s proposals (1874-1940) are still as valid and relevant for the development of theater as they were in their moment of enunciation, almost a century ago. This validity and relevance concern the pedagogical dimension, as well as the scenic and interpretative practices, despite the circumstances of the theatrical philosopher’s death and the historical difficulties that must have been conquered in order to maintain his legacy. This article offers a review of Mayerhold’s main theoretical and practical proposals in order to demonstrate their presence in contemporary and creative bids.